A Study of Writing Proficiency in the Use of Discourse Markers in Iranian EFL Learners' Writing - Kookhaei, Ozra; Amerian, Majid (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The aim of this study was to investigate the use of discourse markers by Iranian EFL learners based on their writing proficiency. The study was conducted at Department of English Language and Literature in university of Arak. 29 participants, 6 males and 23 females, as an intact group, were required to write an essay on an argumentative topic without limit of words and without any instruction. Their writings were analyzed quantitatively using Fraser's (2004) taxonomy of Discourse Markers. The results showed that there is no statistically significant difference between the use of discourse markers and writing proficiency. It was also founded that participants employed a variety of discourse markers with some types used more frequently than others. Coordinate conjunction were the most frequently used, followed by elaborative markers and contrastive markers. Possible implications of the study for language pedagogy have been also discussed.